Enhanced photocatalytic performance of iron oxides@HTCC fabricated from zinc extraction tailings for methylene blue degradation: Investigation of the photocatalytic mechanism - Xue, Yang; Liu, Xiaoming; Zhang, Na; Shao, Yang; Xu, Chunbao Charles (International journal of minerals, metallurgy and materials, 2023)
Photocatalytic processes are efficient methods to solve water contamination problems, especially considering dyeing wastewater disposal. However, high-efficiency photocatalysts are usually very expensive and have the risk of heavy metal pollution. Recently, an iron oxides@hydrothermal carbonation carbon (HTCC) heterogeneous catalyst was prepared by our group through co-hydrothermal treatment of carbohydrates and zinc extraction tailings of converter dust. Herein, the catalytic performance of the iron oxides@HTCC was verified by a nonbiodegradable dye, methylene blue (MB), and the catalytic mechanism was deduced from theoretical simulations and spectroscopic measurements. The iron oxides@HTCC showed an excellent synergy between photocatalysis and Fenton-like reactions. Under visible-light illumination, the iron oxides@HTCC could be excited to generate electrons and holes, reacting with H 2 O 2 to produce ·OH radicals to oxidize and decompose organic pollutants. The removal efficiency of methylene blue over iron oxides@HTCC at 140 min was 2.86 times that of HTCC. The enhanced catalytic performance was attributed to the advantages of iron oxides modification: (1) promoting the excitation induced by photons; (2) improving the charge transfer. Furthermore, the iron oxides@HTCC showed high catalytic activity in a wide pH value range of 2.3–10.4, and the MB removal efficiency remained higher than 95% after the iron oxides@HTCC was recycled 4 times. The magnetically recyclable iron oxides@HTCC may provide a solution for the treatment of wastewater from the textile industry.